A novel multimedia tool to improve bedside teaching of cardiac auscultation. Issue 944 (10th June 2004) - Woywodt, A; Herrmann, A; Kielstein, J T; Haller, H; Haubitz, M; Purnhagen, H
Abstract : Training in cardiac auscultation is a core element of undergraduate teaching but recent studies have documented a remarkable decline in auscultatory skills. Therefore there is an interest in new ways to teach cardiac auscultation. In analogy to phonocardiography, an electronic system for simultaneous auscultation and visualisation of murmurs was sought. For this purpose, an electronic stethoscope was linked to a laptop computer and software created to visualise auscultatory findings. In a preliminary trial in undergraduate students, this approach greatly facilitated teaching. Amalgamating traditional phonocardiography with a multimedia approach, this system represents a novel tool for bedside teaching of cardiac auscultation.